Urbanization and Cultural Shifts: Anthropological Insights into Changing Community Life in Bangkok - (พระมหามิตร ฐิตปญฺโญ), พระครูปริยัติพัฒนบัณฑิต; อ่อนละมุล, กฤษกร (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
This paper examines the profound impact of urbanization on community life and cultural practices in Bangkok, Thailand. As the city rapidly transforms into a major metropolitan hub, traditional norms and communal values face challenges from modern economic demands and global influences. Through an anthropological lens, this study explores how urban expansion reshapes social interactions, cultural identities, and traditional rituals, often leading to fragmented social networks and shifts in family structures. The study highlights the dual impact of urbanization, where on one hand, technological advancements and globalization bring in new opportunities for cultural exchange and economic growth, while on the other, they create social disparities and threaten the continuity of traditional practices. Through a combination of qualitative and quantitative methods, this research provides insights into how communities navigate these changes, balancing the preservation of cultural heritage with the adoption of modern lifestyles. The findings underscore the importance of policy measures that prioritize sustainable urban development and cultural inclusivity to foster a resilient, cohesive community amidst Bangkok’s ongoing transformation.